Do We Need Global Education in the Middle? - Kathleen Malu (Middle Grades Review, 2020)
Do we need global education in the middle? This essay explores the answer to this question using various lenses. A brief overview of the history of global education within the middle school movement is presented as are the relevant goals from This We Believe (NMSA, 2010) and definitions of related terms. Using four dimensions of development—physical, intellectual, moral, and social-emotional—readers are asked to reflect as members of the middle level community and as individuals on their own understandings about the need for global education. The essay ends with recommendations for advancing global education, the author’s response to the question, and several personal anecdotes.
Keywords: middle school; global education; adolescent development; early adolescence